Light, connectivity and place: young people living in a post-industrial town. (October 2018) - Thomas, Gareth M; Elliott, Eva; Exley, Eve; Ivinson, Gabrielle; Renold, Emma
This article reports on a study of how young people in a post-industrial UK town reflect on their sense of health, place and identity. Drawing on 56 qualitative interviews with 14–15 year olds, we explore how young people negotiate public space and how public lighting and darkness affect interactions with their surroundings. The young people provide an insight into how dark places ignite strong feelings of anxiety and danger, deeply fuelled by the environment itself together with rumours, lived knowledge of the locale and symbolic boundaries shaping identities of belonging and exclusion in a context of structural inequality. Young people's understandings of place are configured and energised by multiple sources, such as personal experiences and social locations, material landscapes and powerful discourses – historical and contemporary – conveyed via stories, cautionary tales and stigmatising media representations. We describe how the young people organised a public campaign to, among other things, install streetlights in a dark location. Their activism demonstrates how street lighting, or its absence, is both emblematic of the importance of connectivity and place in their lives, and a manifestation of material (political) abandonment and (class) devaluation.